Early Diagnosis of Critical Postperfusion Circulatory Disorders - L. A. Krichevsky; V. Yu Rybakov; O. G Guseva; A. Yu Lyamin; I. E Kharlamova; A. I. Magilevets (Общая реаниматология, 2012)
Objective: to define the prognostic value of hemodynamic monitoring data and overall oxygen balance in the postperfusion period of cardiosurgical operations. Subjects and methods. Three hundred and fifty-three patients (317 men, 35 women) aged 57±0.6 years, who had been operated on under extracorporeal circulation (78±6 min) with a Swan-Ganz catheter being used, were retrospectively examined. Among the examined, 277 patients had undergone coronary bypass surgery (3.1±0.2 shunts); 18, mitral valve replacement; 42, aortic valve replacement; 9, mitral and aortic valve replacement; and 7 had one-two heart valve replacement with shunting of 2±1 coronary arteries. The left ventricular ejection fraction averaged 48±0.04%. The parameters of central hemodynamics and oxygen balance were recorded when the sternum was brought together. There was a group of those who had been discharged from hospital and a group of those who had died in hospital. The authors used an intergroup comparison of parameters and an analysis of ROC curves, by recording the cut off values. Results. The postperfusion risk factors of hospital mortality were a mean pulmonary artery pressure of more than 29 mm Hg; a pulmonary artery wedge pressure of greater than 16 mm Hg; a cardiac index of less than 2.35 l/min/m2; a stroke volume index of less than 22.7 ml/m2; an indexed oxygen transport of less than 315.6 ml/ml2; a blood lactate level of higher than 4.6 mmol/l; an adrenal dose need of more than 115/ng/kg/min. Left ventricular stroke work indicators, such as a stroke work index of less than 21.2 g”‘Xm”2 and, to the maximum extent, a pump coefficient of lower than 2.8 g”‘Xm”2/mm Hg, have a high degree of accuracy in suggesting the risk of mortality. Conclusion. The invasive monitoring of pulmonary pressure and cardiac efficiency in the postperfusion period permits an objective prediction of a risk for hospital mortality. Key words: cardiosurgery, Swan-Ganz catheter, heart failure, mortality.